Erratum: JANET A. HUNTER & THOMAS H. CRIBB (2012). A cryptic complex of species related to Transversotrema licinum Manter, 1970 from fishes of the Indo-West Pacific, including descriptions of ten new species of Transversotrema Witenberg, 1944 (Digenea: Transversotrematidae). Zootaxa, 3176, 1–44. - Hunter, Janet A.; Cribb, Thomas H. (Zootaxa, 2012)
(Erratum)